2018
DOI: 10.1002/bies.201800063
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β Control of Adaptive Immune Tolerance: A Break From Treg Cells

Abstract: The vertebrate adaptive immune system has well defined functions in maintaining tolerance to self-tissues. Suppression of autoreactive T cells is dependent on the regulatory cytokine transforming growth factor-β (TGF-β) and regulatory T (Treg) cells, a distinct T cell lineage specified by the transcription factor Foxp3. Although TGF-β promotes thymic Treg (tTreg) cell development by repressing T cell clonal deletion and peripheral Treg cell differentiation by inducing Foxp3 expression, a recent study shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…Higher amounts of SOCS1 protein suppress IL-12 and IFNγ signaling inhibiting Th1 cell differentiation, while promoting Th2 cell induction [78,79]. TGF-β as well promotes thymic Treg (tTreg) cell development by inducing FoxP3 expression repressing T cell clonal deletion and peripheral Treg cell differentiation [63,80]. Notably, bovine milk exosomes contain both miR-155 and TGF-β [14,32,45], a fact, that further supports milk exosome-driven maturation of tTregs [18,19].…”
Section: Allergic Diseasesmentioning
confidence: 80%
See 1 more Smart Citation
“…Higher amounts of SOCS1 protein suppress IL-12 and IFNγ signaling inhibiting Th1 cell differentiation, while promoting Th2 cell induction [78,79]. TGF-β as well promotes thymic Treg (tTreg) cell development by inducing FoxP3 expression repressing T cell clonal deletion and peripheral Treg cell differentiation [63,80]. Notably, bovine milk exosomes contain both miR-155 and TGF-β [14,32,45], a fact, that further supports milk exosome-driven maturation of tTregs [18,19].…”
Section: Allergic Diseasesmentioning
confidence: 80%
“…Two independent studies confirmed increased expression of miR-21 in placenta tissue of infants born with macrosomia (birth weight > 4000 g) [99,100]. Milk miR-21, a signature miR of commercial dairy milk and cargo of bovine milk exosomes [71,72,80], most likely reaches the placenta and increases placental and trophoblast growth. miR-21 plays important roles in growth of trophoblastic cell lines [101] and increases PI3K-AKTand mTORC1 signaling by suppression of various key inhibitory checkpoints such as PTEN [11].…”
Section: Fetal Macrosomiamentioning
confidence: 83%
“…Previous studies reported that tumor‐infiltrating immune cells may represent a crucial pathophysiological factor in the onset and progression of glioma . We examined the relationship between COPB2 and six immune cell types that frequently infiltrate the tumor microenvironment, including innate immune cells: neutrophils, tumor‐associated macrophages (TAMs), NK cells, and myeloid‐derived suppressor cells (MDSCs) and adaptive immune cells: CD8+T cells and regulatory T cells (Tregs) . The specific biomarker genes of each immune cell type are displayed in Data S2.…”
Section: Resultsmentioning
confidence: 99%
“…15 We examined the relationship between COPB2 and six immune cell types that frequently infiltrate the tumor microenvironment, including innate immune cells: neutrophils, tumor-associated macrophages (TAMs), NK cells, and myeloid-derived suppressor cells (MDSCs) 16,17 and adaptive immune cells: CD8+T cells and regulatory T cells (Tregs). 18,19 The specific biomarker genes of each immune cell type are displayed in Data S2. Canonical correlation analysis revealed that the transcript levels of COPB2 were positively correlated with the marker gene expression of these six immune cell types in the TCGA datasets ( Figure 5B, P < .001), indicating that glioma patients with COPB2high were prone to have more immune cells infiltrated than glioma patients with COPB2-low.…”
Section: Relationship Between Copb2 and Infiltrating Immune Cellsmentioning
confidence: 99%
“…TGF-β1 belongs to a regulatory cytokine family with pleiotropic functions in many cell type lineages and is a critical differentiation factor for the generation of Treg cells. This cytokine can also induce the production of IL‑10 by Treg cells [23, 34, 35]. Moreover, a recent study showed that TGF-β1 can suppress autoreactive T cells independent of Treg cells [36].…”
Section: Discussionmentioning
confidence: 99%